OPTIMIZATION OF SURGICAL DECOMPRESSION IN PATIENTS WITH CHRONIC CRANIOFACIAL PAIN - Boimuratov Sh.A.,; Asadov Kh.F.,; Asadov Kh.Kh., (Central Asian Journal of Medicine, 2025)
Craniofacial pain significantly impairs quality of life and is often resistant to conservative treatment. In this clinical study, we evaluated the efficacy of peripheral nerve decompression in patients with chronic craniofacial pain. The study involved 100 patients treated at the MEDAS Medical Center between 2018 and 2025. Surgical interventions included decompression of the supraorbital, supratrochlear, auriculotemporal, and zygomaticotemporal nerves. Postoperative outcomes demonstrated an average pain reduction of over 80% and subjective quality-of-life improvement in 90% of cases. These findings confirm the effectiveness of peripheral nerve decompression in selected patients and support its role as a surgical option in craniofacial pain management.